Inflammatory Myofibroblastic Bladder Tumor in a Patient with Von Recklinghausen's Syndrome - Eleftherios Chatzidarellis; Evangelos Mazaris; Andreas Skolarikos; Demonakou Maria; Iraklis Mitsogiannis; Nafsika Mousiou; Apostolos Bisas (Case Reports in Medicine)
Myofibroblastic tumor, also known as inflammatory pseudotumor or pseudosarcoma, is a benign tumor with mesenchymal origin. Bladder location is very uncommon. We report the case of a 58-year-old man with a history of von Recklinghausen's disease who complained for painless macroscopic hematuria 5 months after suprapubic prostatectomy. The radiograph evaluation revealed a bladder tumor, and the pathologic examination following a transurethral resection showed inflammatory myofibroblastic tumor of the bladder. The patient finally underwent a radical cystectomy due to the uncertain pathogenesis of inflammatory myofibroblastic tumor as well as the rarity of cases published on bladder tumors in Von Recklinghausen's patients.